Mathematical models of hybrid crypto - code constructions on damaged codes - Yevseiev, S. P.; Bakirova, Lala; Sushchenko, Mariia (Національний технічний університет "Харківський політехнічний інститут", 2019)
The subject are mathematical models of building hybrid (complex) cryptosystems based on Mac-Elis crypto-code constructions on damagedcodes. The purpose of this work is cryptographic mechanisms design in post-quantum cryptography to provide basic security services. The use of crypto-code structures in the mechanisms of strong authentication based on OTP passwords Development of practical algorithms for their implementation based on the proposed mathematical models. The tasks: analysis of the main threats of using OTP passwords; basics of construction and using multi-channel cryptography systems on damaged codes; a formal description of mathematical models of hybrid crypto-code constructions on damaged codes based in the modified McEliece and Niederreiter crypto-code systems in elliptic curves; development of algorithms for data encryption and decryption at the Niederreiter-McEliece hybrid crypto code constructions (НССС). Conclusion: The comprehensive protection mechanisms proposed in the article ensure the use of a strong authentication protocol in post-quantum cryptography based on OTP passwords. The use of damaged codes extends the possibilities of using crypto-code structures by significantly reducing the power of the alphabet while maintaining the required level of cryptographic resistance.

Предметом дослідження є математичні моделі побудови гібридних (комплексних) криптосистем на основі крипто-кодових конструкцій Мак-Еліса на збиткових кодах. Метою даної роботи є побудова криптостійкіх механізмів в умовах постквантовой криптографії для забезпечення основних послуг безпеки. Використання крипто-кодових конструкцій в механізмах суворої автентифікації на основі ОТР-паролів. Розробка практичних алгоритмів їх реалізації на основі пропонованих математичних моделей. Завдання, які необхідно вирішити – аналіз основних загроз використання OTP-паролів; аналіз основ побудови і використання багатоканальних криптографічних систем на збиткових кодах; формальний опис математичних моделей гібридних крипто-кодових конструкцій на збиткових кодах на основі модифікованих крипто-кодових систем Мак-Еліса і Нідеррайтера на модифікованих еліптичних кодах; розробка алгоритмів шифрування і дешифрування даних в гібридних крипто-кодових конструкціях Мак-Еліса – Нідеррайтера. Висновок: запропоновані в статті комплексні механізми захисту забезпечують використання протоколу суворої автентифікації в умовах постквантовоїкриптографії на основі ОТР-паролів. Використання збиткових кодів розширює можливості використання крипто-кодових конструкцій за рахунок значного зниження потужності алфавіту зі збереженням необхідного рівня криптостійкості.
Математичні моделі крипто-кодових конструкцій на збиткових кодах
Keywords: McEliece crypto code constructions; cryptography on damages codes; крипто-кодові конструкції Мак-Еліса; криптографія на збиткових кодах